Analysis of Flow Characteristics of Slurry Transportation System - Singh, Mani Kanwar (My University, 2017)
Coal is a major source of energy. In India, about 70% electricity generation is produced by combustion of pulverized coal in thermal power plants. The major challenge throughout the world is the efficient utilization of a fuel in power generation. The concentrated coal-water slurry contains 60–70% coal powder that is used as a liquid fuel for the replacement of oil as a fuel. The maximum concentration of slurry with appreciable viscosity increases the efficiency of transportation of the coal-water slurry in pipelines for fuel generation. Combustion of coal in power plants generates a huge quantity of inorganic residues like bottom ash and fly ash, which have numerous ecological problems. Generally the coal ash is being transported hydraulically to ash pond through slurry pipelines at low solid concentrations, which is extremely uneconomical. The efficient and economical transportation of coal water slurry as well as coal ash slurry is a major challenge. The parameters, which have significant effect on the slurry transportation system, are slurry concentrations and slurry rheology. The economy of slurry transportation is achieved by transporting higher concentration of slurry having minimum viscosity so that the power required for transportation will be minimum. So the understanding of impact of these parameters on slurry transportation is necessary for efficient designing of slurry transportation system. The present study is concerned with the analysis of impact of slurry rheology and slurry concentration on slurry transportation in a pipeline. The coal samples are collected directly from the coalmines of Makum coalfield of Dibrugarh district of Assam for the present study. The coal samples are prepared by crushing with laboratory-size ball mill to the different fractional sizes required for experiments. The Makum field coal is also used for power generation in Guru Nanak Dev thermal power plant, Bathinda, Punjab, India. The fly ash and bottom ash produced during the power generation are collected from Guru Nanak Dev thermal power plant for the present study. The various bench scale tests like particle size distribution, static settled concentration, specific gravity and potential of hydrogen value are performed to study the physiochemical properties of coal. The morphology of coal and coal ash samples is determined by scanning electron microscopy (SEM). The leaching test of heavy metals from fly ash and bottom ash is investigated in order to predict the environmental effect from the ash disposal system. From the leaching test, it is also observed that the leached concentration of the tracing elements in the fly ash is more compared with the bottom ash at the same liquid to solid ratio. The rheological characteristics of coal water and fly ash–water slurries have been studied to facilitate their conveying at higher concentrations. The rheological experiments of coalwater slurry are conducted in the solid concentration range of 30-60% (by weight). The apparent viscosity and shear stress are measured at shear rate ranging from 0–600 s-1. The rheological behavior of coal water slurry is conducted for both unimodal and bimodal particle size distribution of coal and It is observed that with 30% addition of coarse size coal particle with finer coal particles for a slurry concentration shows the minimum apparent viscosity. Similarly the rheology of fly ash slurry is investigated with and without addition of bottom ash in the overall concentration range of 30-60% (by weight) and the maximum apparent viscosity reduction of fly ash slurry is found with 20% addition of bottom ash whereas marginal reduction in apparent viscosity is observed with 10 and 30% addition of bottom ash. The present study is also concerned with determination of the pressure drop characteristics during the transportation of coal slurry as well as coal ash slurry by both experimentally and numerically. The experimental results show that the pressure drop is increased with increase in solid concentration. It is also found that the slurry prepared by adding the 30% of coarser particles of coal in finer particles significantly reduces the pressure drop as the viscosity is significantly reduced. Similarly the experimentation is also performed to investigate the effect of addition of bottom ash particles on pressure drop characteristics of fly ash slurry and it is found that the maximum reduction in pressure drop is observed with 20% addition of bottom ash. The numerical simulation is made using FLUENT software and it is found that the results obtained using SST k-ω turbulence model is in good agreements with the experimental data. Taguchi method is used to identify the various influencing parameters, which have significant effect on pressure drop during the transportation of slurry in pipeline. Flow velocity is found most significant parameter followed by addition of additive composition and solid concentration.
Keywords: SLURRY; TRANSPORTATION SYSTEM